Answer:
The solved given expression is
[tex]\frac{-3^4x-3^4}{(-3^2)^3}=-\frac{(x+1)}{9}[/tex]
Step-by-step explanation:
Given expression is [tex]\frac{-3^4x-3^4}{(-3^2)^3}[/tex]
To solving the given expression as below :
[tex]\frac{-3^4x-3^4}{(-3^2)^3}[/tex]
[tex]\frac{-3^4x-3^4}{(-3^2)3}=\frac{3^4(-x-1)}{(-3^2)3}[/tex]
[tex]=\frac{-3^4(x+1)}{(3^2)3}[/tex] ( by using the property [tex](a^m)^n=a^{mn}[/tex] )
[tex]=\frac{-3^4(x+1)}{3^6}[/tex]
[tex]=\frac{-(x+1)}{3^6.3^{-4}}[/tex] ( by using the property [tex]a^m=\frac{1}{a^{-m}}[/tex] )
[tex]=\frac{-(x+1)}{3^{6-4}}[/tex] ( by using the property [tex]a^m.a^n=a^{m+n}[/tex] )
[tex]=-\frac{(x+1)}{3^2}[/tex]
[tex]=-\frac{(x+1)}{9}[/tex]
Therefore [tex]\frac{-3^4x-3^4}{(-3^2)^3}=-\frac{(x+1)}{9}[/tex]
Therefore the solved given expression is
[tex]\frac{-3^4x-3^4}{(-3^2)^3}=-\frac{(x+1)}{9}[/tex]